GA based hybrid tier packing approach for three dimensional packing - Poh, Terence Eng Hua (2008)
This thesis proposed the Hybrid Tier Packing Approach for solving three dimensional packing problems. HTPA uses both heuristic and GA to conduct its packing for each tier. Heuristic packing is used for solving simpler tier packing problems while GA packing is used for solving the tougher and more complex tier packing problems. By applying suitable packing methods for solving the two difficulty classes of tier packing problems, optimal packing results can be obtained in a time efficient manner.